Bcl-2-dependent upregulation of autophagy by sequestosome 1/p62 in vitro - Zhou Liang; Wang Hong-feng; Ren Hai-gang; Chen Dong; Gao Feng; Hu Qing-song; Fu Chen; Xu Ran-jie; Ying Zheng; Wang Guang-hui (Acta Pharmacologica Sinica, 2016)
Liang ZHOU1, Hong-feng WANG2, Hai-gang REN2, Dong CHEN2, Feng GAO1, Qing-song HU2, Chen FU1, Ran-jie XU1, Zheng YING2, *, Guang-hui WANG1, 2, * 1Key Laboratory of Brain Function and Disease, School of Life Sciences, University of Science & Technology of China, Chinese Academy of Sciences, Hefei 230027, China; 2Laboratory of Molecular Neuropathology, Department of Pharmacology, Soochow University College of Pharmaceutical Sciences, Suzhou 215123, China Aim: To investigate whether sequestosome 1/p62 (p62), a key cargo adaptor protein involved in both the ubiquitin-proteasome system and the autophagy-lysosome system, could directly regulate autophagy in vitro. Methods: HEK 293 cells or HeLa cells were transfected with p62-expressing plasmids or siRNA targeting p62. The cells or the cell lysates were subsequently subjected to immunofluorescence assay, immunoprecipitation assay, or immunoblot analysis. In vitro pulldown assay was used to study the interaction of p62 with Bcl-2. Results: Overexpression of p62 significantly increased the basal level of autophagy in both HEK 293 cells and HeLa cells, whereas knockdown of p62 significantly decreased the basal level of autophagy. In vitro pulldown assay showed that p62 directly interacted with Bcl-2. It was observed in HeLa cells that p62 co-localized with Bcl-2. Furthermore, knockdown of p62 in HEK 293 cells significantly increased the amount of Beclin 1 that co-immunoprecipitated with Bcl-2. Conclusion: p62 induces autophagy by disrupting the association between Bcl-2 and Beclin 1. Keywords: autophagy; sequestosome 1/p62 (p62); LC3; Bcl-2; Beclin 1; HEK 293 cell; HeLa cell; in vitro pulldown assay This work was supported in part by the National High-Tech Research and Development Program of China 973 Projects (2011CB504102), and the National Natural Sciences Foundation of China (91132723 and 31200803). * To whom correspondence should be addressed. E-mail wghui@ustc.edu.cn (Guang-hui WANG); zheng.ying@suda.edu.cn (Zheng YING) Received 2012-12-06 Accepted 2013-01-29